Virtual Plan-Design-Build for Capstone Projects in the School of Architecture: CM & BIM Studios in Five-Year B.Arch. Program. Issue 2 (1st May 2016) - Jung, Youngsoo; Kim, Hyosun; Kim, Namjoon
Abstract: Diversification in project delivery methods (PDM) over the last two decades has significantly changed the roles of architects, engineers, and contractors in the construction industry. Under the emerging alternative PDMs, the common requirements for architects include ′planning capability′, ′integrated understanding of design and construction′, and ′IT skills′ in addition to traditional architects′ qualifications. In order to meet these requirements, a novel approach to educating future architects was attempted at Myongji University as a capstone project for the 5-year architecture program. This studio was entitled CM & BIM studio focusing on three objectives in design studios; planning, life-cycle integration, and building information modeling (BIM). This paper proposes a curriculum for the CM & BIM studio with detailed teaching objectives and student deliverables. Educational requirements in the age of new architecture were identified first. The CM & BIM studio in 2012 as a case study was introduced in order to validate the adaptability of proposed curriculum. Comments from professors and architects verified and encouraged the promising educational results intended in this paper. Finally, findings and lessons learned are also briefly discussed.